Development of Flexible Polyurethane Nanostructured Biocomposite Foams Derived from Palm Olein-Based Polyol - Srihanum Adnan; Tuan Noor Maznee Tuan Ismail; Norhayati Mohd Noor; Nik Siti Mariam Nek Mat Din; Nurul ‘Ain Hanzah; Yeong Shoot Kian; Hazimah Abu Hassan (Advances in Materials Science and Engineering)
This study examined the effect of organoclay montmorillonite (OMMT) on the mechanical properties and morphology of flexible polyurethane/OMMT nanocomposite (PU/OMMT) foams prepared from petroleum- and palm olein-based polyols. Palm-based PU foams exhibited inferior mechanical strength as compared to neat petroleum PU foams. However, addition of OMMT significantly improved the foams strength of flexible polyurethane/OMMT nanocomposite foams prepared from palm olein-based polyol (PU bionanocomposite foam). The morphology analysed by scanning electron microscopy (SEM) showed that the cell size of the foam decreased with increasing OMMT content. PU bionanocomposite foam with 5 wt% of OMMT had the most improved tensile (63%) and tear (48%) strengths compared to its neat counterpart. Transmission electron microscopy (TEM) revealed the exfoliated structure of the respective foam. It was concluded that OMMT improved mechanical properties and morphology of PU foams.